L-carnitine reduces hospital admissions in patients with hepatic encephalopathy. Issue 2 (February 2021) - Tani, Joji; Morishita, Asahiro; Sakamoto, Teppei; Takuma, Kei; Nakahara, Mai; Fujita, Koji; Oura, Kyoko; Tadokoro, Tomoko; Mimura, Shima; Nomura, Takako; Yoneyama, Hirohito; Kobara, Hideki; et al.
Abstract : Aim: The aim of this study was to determine whether oral L-carnitine administration reduces the blood ammonia concentration and number of hospital admissions for hepatic encephalopathy in patients with advanced cirrhosis. Methods: Of 68 patients with hepatic encephalopathy treated with oral L-carnitine supplementation from April 2013 to March 2016, we enrolled 19 patients who had received full standard treatment. We analyzed blood ammonia concentration, number of hospital admissions, and prognosis to determine how effective L-carnitine was in achieving mid-term to long-term suppression of recurrent hepatic encephalopathy. Results: Median blood ammonia concentrations at the start, 1 week, 12 weeks, 24 weeks, and 48 weeks were 159, 79, 75, and 82 μg/dL, respectively. Blood ammonia concentrations 12 week, 24 weeks, and 48 weeks after L-carnitine administration were significantly lower than those at the start ( P < 0.0001, respectively). During the 3 years prior to oral L-carnitine administration, the enrolled patients were hospitalized a total of 29 times for hepatic encephalopathy. However, during the 3 years following oral L-carnitine administration, they were admitted a total of six times for hepatic encephalopathy ( P < 0.001). Median survival time was 40.9 months. Child-Pugh scores before and after oral L-carnitine administration differed significantly, whereas liver reserve function, nutritional status, and muscle index did not change significantly. Conclusions: Oral L-carnitine administration is effective and free of adverse effects in patients with hyperammonemia and reduces the number of hospital admissions for hepatic encephalopathy.